2021
DOI: 10.1371/journal.pone.0245009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in social connection during COVID-19 social distancing: It’s not (household) size that matters, it’s who you’re with

Abstract: To slow the transmission of COVID-19, countries around the world have implemented social distancing and stay-at-home policies—potentially leading people to rely more on household members for their sense of closeness and belonging. To understand the conditions under which people felt the most connected, we examined whether changes in overall feelings of social connection varied by household size and composition. In two pre-registered studies, undergraduates in Canada (NStudy 1 = 548) and adults primarily from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 38 publications
7
71
2
Order By: Relevance
“…Fears of family contracting COVID-19 are consistent with emerging literature on the subject [ 45 ]. The specific stress of social distancing reported by respondents is also consistent with findings in the literature [ 46 ]. The findings regarding the added stress of domestic relationships is consistent with prior literature that links increases in domestic stress and violence during natural disasters [ 47 ] and the COVID-19 pandemic [ 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…Fears of family contracting COVID-19 are consistent with emerging literature on the subject [ 45 ]. The specific stress of social distancing reported by respondents is also consistent with findings in the literature [ 46 ]. The findings regarding the added stress of domestic relationships is consistent with prior literature that links increases in domestic stress and violence during natural disasters [ 47 ] and the COVID-19 pandemic [ 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…Third, negotiating what constitutes appropriate household pandemic behaviors (e.g., how often to sanitize surfaces) with adult co-habitants that hold different standards could be stressful. Fourth, it is possible that the amount of social support received from co-habitants, and thus the extent to which they reduce or exacerbate the stress-life satisfaction association, depends not merely on the number of co-habitants, but on who they are (Okabe-Miyamoto et al, 2021). Future research can investigate which, if any of these explanations accounts for the partial support of our moderation hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…However, subsequent analyses revealed that having a romantic partner, being younger in age (<65 years, among women), as well as having lower social support and higher psychological distress predicted greater decreases in loneliness over time. The potential importance of living with a partner has been observed in other longitudinal samples utilizing preregistered analysis plans (e.g., Okabe-Miyamoto et al, 2021), suggesting that living with a romantic partner during this challenging time may offer unique benefits.…”
Section: Loneliness and Social Connectionmentioning
confidence: 89%